Diskriminasi terhadap Penyandang Disabilitas dalam Drama Perfect World - Trisnayola, Fadira; Lestari, Dwi Astuti Retno; Fredy, Mochammad (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2025)
This study aimed to examine the forms of discrimination experienced by people with disabilities as portrayed in the Japanese drama Perfect World, as well as the ways in which the characters responded to such experiences. A qualitative descriptive method was employed, with data collected using the observation and note-taking technique. Scenes and dialogues from the drama were analyzed to identify patterns of discriminatory behavior and coping responses. The findings revealed three main types of discrimination: explicit and intentional discrimination, subtle and unconscious discrimination, and structural or organizational discrimination. In response to these forms of discrimination, the characters employed various coping strategies, including problem-focused and emotion-focused coping, as well as open and covert forms of resistance. Among these responses, emotion-focused coping and open resistance were the most frequently used strategies.